PEMILIHAN PRESIDEN SECARA LANGSUNG DAN IMPLIKASINYA TERHADAP SISTEM KETATANEGARAAN INDONESIA - M. Guntur Hamzah (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2003)
“Direct Presidential election is based on people’s will to determine their own national leaders. It leads to the changing MPR existence as an institution that holds people sovereignty and is authorized to appoint President and Vice President. Another point that should be clearly thought over on direct Presidential election is terms and mechanism of the election implementation.